Optimización del proceso de gestión de una planta de manipulación de sustancias peligrosas - Belmont, Alvaro Francisco (2019)
This work is based on a family business that opened its doors in 2004 and today is among the leaders of oil and dangerous substances transportation in northern Argentina. It is dedicated to the distribution of dangerous substances such as lubricants, diesel, mining oil, collection of contaminated oils, and others; covering the areas of Salta, Catamarca, Tucumán, Santiago del Estero, Jujuy, Chaco and Formosa. As the years go by, it has positioned its name in the logistics market in front of its customers, for its excellent quality of service and the predisposition of the human resource that represents it. Those type of companies be sustainable and must look for a process of continuous improvement that concentrates the objectives of each area. Therefore, communication between areas, the crossing information, the constant training of human resources and the willingness to grow every day, should constitute the engine to remain positioned in face to competitors. The objective, will be provide the company with tools that allow it to achieve a new management control system, in the areas that present bigger difficulties in the development of its processes.